2021
DOI: 10.3390/en14217387
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Prediction Error in Regression Air Quality Models

Abstract: Combustion of energy fuels or organic waste is associated with the emission of harmful gases and aerosols into the atmosphere, which strongly affects air quality. Air quality monitoring devices are unreliable and measurement gaps appear quite often. Missing data modeling techniques can be used to complete the monitoring data. Concentrations of monitored pollutants can be approximated with regression modeling tools, such as artificial neural networks. In this study, a long-term set of data from the air monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The RMSE statistic allows for a term-by-term comparison of the actual difference between the estimated and measured values, providing information on a model's short-term performance. Performance of the model improves as the value decreases (Hoffman 2021). The verification of experimental findings is frequently done in forecasting, climatology, and regression analysis.…”
Section: Idw Cross-validation Results For Pm25 Concentration Measured...mentioning
confidence: 98%
“…The RMSE statistic allows for a term-by-term comparison of the actual difference between the estimated and measured values, providing information on a model's short-term performance. Performance of the model improves as the value decreases (Hoffman 2021). The verification of experimental findings is frequently done in forecasting, climatology, and regression analysis.…”
Section: Idw Cross-validation Results For Pm25 Concentration Measured...mentioning
confidence: 98%
“…Research can also be conducted on segment modeling. Since differences in modeling accuracy were found in different concentration subranges [66,67], the improvement of modeling quality was tested by replacing a single model with a group of models dedicated to specific subranges of pollutant concentrations [68]. Promising results were obtained for segmented modeling.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The data also include two variables describing the time: day and hour. These two variables were converted to numeric form following the procedure described in [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…In regression modeling, it was found that the application of one neural network to the entire range of concentrations of the predicted pollutant resulted in different prediction accuracies in the concentration sub-ranges [ 38 , 39 ]. It was considered advisable to replace one neural network with several networks (sub-models), each of which would be adjusted to specific concentration sub-ranges [ 39 ]. The use of several sub-range models should improve the accuracy of the prediction.…”
Section: Introductionmentioning
confidence: 99%